2016
DOI: 10.1017/s0954102016000055
|View full text |Cite
|
Sign up to set email alerts
|

In situ foraminifera in grounding zone diamict: a working hypothesis

Abstract: The ice-proximal diamict sediment deposited on the foreset of a grounding zone wedge in Glomar Challenger Basin on the eastern Ross Sea continental shelf yielded a low abundance assemblage of foraminifera at two piston core sites. We found 302 small well-preserved specimens representing 18 species of benthic foraminifera from 825 ml of sediment. Only three poorly preserved specimens of the planktonic foraminifera Neogloboquadrina pachyderma (sinistral) were found. Our combined analyses of preservation state, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Our results confirm that proximal glacimarine facies have the potential to bear in situ foraminifera when collected from foresets and toes of GZWs in the western Ross Sea, supporting previous studies in the eastern Ross Sea (Bart & Cone, 2012; Bart et al, 2016; Bart et al, 2018; Majewski et al, 2018). However, abundant, post‐LGM foraminifera were encountered only in the four cores (KC17, KC30, KC48, and KC49; Table 2 and Figure 7).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results confirm that proximal glacimarine facies have the potential to bear in situ foraminifera when collected from foresets and toes of GZWs in the western Ross Sea, supporting previous studies in the eastern Ross Sea (Bart & Cone, 2012; Bart et al, 2016; Bart et al, 2018; Majewski et al, 2018). However, abundant, post‐LGM foraminifera were encountered only in the four cores (KC17, KC30, KC48, and KC49; Table 2 and Figure 7).…”
Section: Discussionsupporting
confidence: 91%
“…It is less dominant in core KC17 from Pennell Trough, especially in intervals lacking a coarser (>63 μm) fraction (Figure 7). A similar assemblage dominated by G. subglobosa was described by Melis and Salvi (2009) from proximal glacimarine sediments of the western Ross Sea and in Glomar Challenger Basin in the eastern Ross Sea (Bart et al, 2016).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Where possible, we used monospecific samples comprised of benthic G. biora and T. earlandi (and in one instance planktonic N. pachyderma ) that were the most numerous and fairly massive (Table 1 ). The good to pristine preservation of these foraminifera, along with the lack of clearly reworked specimens, that could be identified either by different coloration, sediment filling 33 and/or presence of extinct species 34 , indicates that practically all specimens could be considered as being in situ 22 , 35 . Rare specimens showing signs of etching, found especially among Cibicides or foraminiferal specimens in cores from the middle continental shelf, although most likely also being in situ , were not used for radiocarbon analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Bart et al . 35 showed that calcareous foraminifera from GZWs can be used for radiocarbon dating of marine diamicts from the eastern Ross Sea if they are selected with considerable care.…”
Section: Discussionmentioning
confidence: 99%